2017
DOI: 10.1007/5584_2017_123
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Week Fecal Microbiota Transplantation Course in Pediatric Patients with Inflammatory Bowel Disease

Abstract: Dysbiosis plays a major role in the etiology of inflammatory bowel disease (IBD). Fecal microbiota transplantation (FMT) is a new promising option for IBD treatment. We aimed to assess the effectiveness of a two-week FMT course in children with IBD. Ten patients, 10-17 years of age with moderate to severe IBD received a course of eight doses of freshly prepared FMT via a naso-duodenal tube or gastroscopy. All of the patients had pancolitis. There were eight cases of ulcerative colitis (UC) and two of Crohn's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…Our previously reported data in 2015 based on 30 CD patients [ 6 ], and an open label study in 2016 from Boston based on 19 patients [ 19 ], demonstrated a similar overall safety of FMT. A study involving two children from Poland reported that the observed side effects of FMT for CD were self-limiting and benign [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previously reported data in 2015 based on 30 CD patients [ 6 ], and an open label study in 2016 from Boston based on 19 patients [ 19 ], demonstrated a similar overall safety of FMT. A study involving two children from Poland reported that the observed side effects of FMT for CD were self-limiting and benign [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the present outcome showed a small trend of decreasing clinical efficacy, there was no significant difference in the rate of clinical response or clinical remission between the two groups of different methods. Importantly, the reported clinical response of FMT for CD from different centers was variable [ 2 7 , 19 , 20 , 22 ]; however, the clinical efficacy in all of our previous studies kept stable [ 2 , 6 , 7 ]. Interestingly, the present results demonstrated that CD patients with AEs might have decreased benefits from FMT than those patients without AEs.…”
Section: Discussionmentioning
confidence: 99%
“…45 Of note, studies using delivery of FMT using the upper gastrointestinal route tend to utilize lower volumes of donor stool in comparison to delivery via the lower gastrointestinal route. 38,46,47 Conceivably, limited exposure of the host immune system to the novel microbiota in the colon is associated with a lower likelihood of worsening in IBD disease activity. This rate is driven mainly by uncontrolled observation studies.…”
Section: Discussionmentioning
confidence: 99%
“…The stool type subgroup analysis revealed clinical remission rates of 29.1% for fresh fecal material [17-20, 22-26, 28-32, 35, 38, 42, 46, 47, 51, 52], 44.2% for frozen fecal material [21,27,39,45,49,50], 57.2% when both types of stool were used [36,48,53], and 66.5% for capsules [37,43], with a statistical difference observed among the groups (p = 0.036). Two articles did not report the type of stool used for the FMT [33,34] (Table 2, S4 Fig).…”
Section: Proportions Meta-analysesmentioning
confidence: 99%